Ayurvedic Management of Nontoxic Nodular Goitre with Haemorrhagic Nodules, Calcification and Atypia – A Case Report - Sabade, Mahesh (International Research Journal of Ayurveda & Yoga, 2022)
Ayurvedic treatment has been beneficial in treating disorders related to metabolism. In this case report, a condition involving thyroid gland, manifesting haemorrhagic nodules with the presence of atypical cells was treated with Ayurveda. It showed encouraging results in this case study. Ayurvedic herbo mineral preparations used here proved effective in correcting the morphology of the thyroid cells from atypical nature to normal and also healing the haemorrhagic status of the nodules. The probable hazards of the condition and related management including removal of thyroid gland were prevented. A long term ayurvedic management was planned for better results. This is an observation based case report and has limitations in comparison to a clinical trial. Ayurvedic management can be effective in conditions that can be considered as new-age diseases when appropriate thought process is applied. Thyroid disorders are few of these conditions. Similar plan can be thought of in various such unmentioned disorders in ayurveda. This may be a guiding case report.